2018
DOI: 10.1088/1674-1056/27/10/106102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Al component content on optoelectronic properties of Al x Ga 1− x N

Abstract: Using density functional theory, the electronic structures, lattice constants, formation energies, and optical properties of Al x Ga 1−x N are determined with Al component content x in a range from 0 to 1. As x increases, the lattice constants decrease in e-exponential form, and the band gap increases with a band bending parameter b = 0.3954. The N-Al interaction force in the (0001) direction is greater than the N-Ga interaction force, while the N-Al interaction force is less than the N-Ga interaction force in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The bolts, welds, holes and the supports of the cryopipe (9 and 80 K) are not considered in the thermal model. Sharing nodes are used at the interfaces between all of the components [15][16][17][18].…”
Section: The Finite Element Modelmentioning
confidence: 99%
“…The bolts, welds, holes and the supports of the cryopipe (9 and 80 K) are not considered in the thermal model. Sharing nodes are used at the interfaces between all of the components [15][16][17][18].…”
Section: The Finite Element Modelmentioning
confidence: 99%
“…increased by binding them to organic ligands [11][12][13] and embedding them inside inorganic matrices [9,10,[14][15][16][17], organic polymers [18][19][20][21][22][23], or metal-organic frameworks [24]. For example, it has recently been shown that a polystyrene shell around CH 3 NH 3 PbBr 3 HP NP promotes better water resistance [25], while deposition of such nanoparticles in a porous Al 2 O 3 matrix provides retention of their high PLQY [26].…”
mentioning
confidence: 99%